Governance of the Social Safety Net in Bangladesh: A Study on the Employment Generation Programme for the Poorest. (June 2023) - Kaiser, Z. R. M. Abdullah; Uddin, Nasir; Yaqub, Mohammad
The article aims to assess the governance of the social safety net programme in Bangladesh. The data were collected from the beneficiaries and stakeholders of the employment generation programme for the poorest scheme of the government of Bangladesh. A total of 150 respondents were selected randomly, and data and information were collected using a structured questionnaire for interviews and a guideline for focus group discussions. The analysis shows that beneficiaries and stakeholders of the programme are mostly satisfied with the quality and timeliness of work, beneficiaries selection and benefits distribution process, but many respondents expressed their dissatisfaction with monitoring and wage rates. Furthermore, the research reveals several factors that contribute to establishing poor governance, such as weak monitoring, absenteeism, proxy work and inappropriate project selection. The finding suggests that it is necessary to make local-level institutions fully operational, determine district-wise wage rates and enhance the monitoring process to achieve the programme objectives.